2014
DOI: 10.1080/07373937.2014.952381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound and Microwave Pretreatments of Apple Before Spouted Bed Drying on Rate of Dehydration and Physical Properties

Abstract: Pretreatments of fruits before drying have been proposed as alternative way to improve the quality of dried fruits and reduce drying time. In the present study, the effects of different pretreatments (ultrasound and microwave) on apple cubes prior to spouted bed drying were investigated. Ultrasound pretreatment resulted in a great loss of sugars (25.7% for 15 min) compared to microwave pretreatment, where little rise in sugar content was observed (1.6% at 300 W). Ultrasound pretreatment improved the drying rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 38 publications
9
66
0
Order By: Relevance
“…Increase in rehydration ratio with IR pretreatment, than only KMS is observed in both the drying method. These results are in line with those reported by Mothibe et al [9] , that ultrasound pretreatment before drying improves the rehydration capability of dried products. Apple slices treated with KMS (T1) and freeze dried had marginally higher rehydration ratio (3.86) compared to that of T1 treated and HA dried (3.21).…”
Section: Dpph Radical-scavenging Activitysupporting
confidence: 94%
See 2 more Smart Citations
“…Increase in rehydration ratio with IR pretreatment, than only KMS is observed in both the drying method. These results are in line with those reported by Mothibe et al [9] , that ultrasound pretreatment before drying improves the rehydration capability of dried products. Apple slices treated with KMS (T1) and freeze dried had marginally higher rehydration ratio (3.86) compared to that of T1 treated and HA dried (3.21).…”
Section: Dpph Radical-scavenging Activitysupporting
confidence: 94%
“…A few reports are available on drying of apple slices of various shapes in tray dryers with and without air circulation, in fluidized bed dryer or using superheated steam. [5][6][7][8][9][10][11] Long drying times required in case of convective drying could deteriorate product quality in terms of flavour, colour and nutrients, besides affecting texture. [12] More rapid, safe and controllable drying methods are required to overcome these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such application found that both microwave and ultrasonic pretreatments of apple cubes redistributed moisture within the product, and that the ultrasound treated samples exhibited higher drying rates than those treated by MW in subsequent spouted bed drying. [148] Similar results were found when MW and pulsedelectric field (PEF) pre-treatments were studied for their application to raisin production, where it was found that both had an effect on drying rate. [149] PEF has also been applied in order to disrupt the cellular structure of food products prior to air drying.…”
Section: Operationssupporting
confidence: 75%
“…The present experiment revealed that yellow peach fruit had only one signal peak. The T 2 was found at 500-1000 ms, and the free water was shown in the signal area of A 2 (Shao and Li, 2013), which is earlier than that of potato (Liu and Wang, 2014), sweet corn (Shao and Li, 2013), and meat (Siciliano et al, 2013), but similar to that of apple (Mothibe et al, 2014).…”
Section: Discussionmentioning
confidence: 95%